PERENCANAAN PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) DI SUNGAI YEH DIKIS BANJAR LEBAH KABUPATEN TABANAN MENGGUNAKAN GENERATOR AC - Sahabat Nazara; Cokorde Gede Indra Partha; I Wayan Sukerayasa (Program Studi Teknik Elektro UNUD, 2023)
Renewable energy is a naturally available energy source in nature, including wind, bioenergy, geothermal heat, solar radiation, flowing and high-drop water, as well as oceanic motion and temperature changes. Planning for the Micro Hydro Power Plant (PLTMH) in Yeh Dikis Banjar Lebah, Tabanan Regency, utilizes an AC generator as one of the ways renewable energy can be utilized. The literature review and observation methods were employed in this study to determine the turbine rotation speed required to drive the generator and to select the appropriate generator. Yeh Dikis River in Banjar Lebah, Tabanan Regency has a capacity of 30.62 kW, with a crossflow turbine operating at a rotation speed of 539 rpm and a torque of 321.81 Nm. The calculation results indicate that the generator capacity to be used is 21.55 kVA. Therefore, the chosen generator is the Generator Head Alternator with a rotation speed of 1500 rpm, providing an output power of 15.516 kW, a generator current of 31.75 A, and an efficiency of 90%. Since the turbine and generator rotation speeds are not compatible, a mechanical transmission system is required, achieved by designing pulley and belt ratios.